Influence of Mixing Speed on Dough Microstructure and Rheology - Silvia Mironeasa; Georgiana Gabriela Codină (Food Technology and Biotechnology, 2013)
The influence of mixing speed (80, 160 and 250 rpm) on dough microstructure and dough rheology has been investigated using epifluorescence light microscopy and Mixolab device. Principal component analysis was used to highlight the association between some analytical characteristics of wheat flour and Mixolab parameters during the initial kneading process (1st stage) at different mixing speeds. Significant correlations were found between the gluten deformation index and some Mixolab parameters (dough development time, work input at maximum consistency during stage 1) at all used mixing speeds. For each of the mixing speeds used, a mathematical model was developed using dough consistency and work input at different processing times (1, 2, 3, 4 and 5 min) as variables. The dough consistency and time point parameters give the best explanation of the variation of the work input, at the same mixing speeds and times.